Groom News and McLean News - (:unkn) unknown (My University, 1998)
Notice - The McLean News and Groom News newspapers were printed in a single issue for both newspapers. Digital PDF files here represent the natural order of the newspapers as represented on the microfilm from which these scans are derived. Depending on the issue filmed, the order of pages may vary.
The McLean News and Groom News merged into a single volume in 1985. One section of the newspaper is dedicated to the news of Groom, and another section is dedicated to the news of McLean. The newspaper continues to be printed in this format today.
Keywords: McLean (Tex.)--Newspapers.; Groom (Tex.) -- Newspapers.; Gray County (Tex.)--Newspapers.; Carson County (Tex.) -- Newspapers.